Efficiency evaluation for remediating paddy soil contaminated with cadmium and arsenic using water management, variety screening and foliage dressing technologies. (1st April 2016) - Liao, Guojian; Wu, Qianhua; Feng, Renwei; Guo, Junkang; Wang, Ruigang; Xu, Yingming; Ding, Yongzhen; Fan, Zhilian; Mo, Liangyu
Abstract: Paddy soils in many regions of China have been seriously polluted by multiple heavy metals or metalloids, such as arsenic (As), cadmium (Cd) and lead (Pb). In order to ensure the safety of food and take full advantage of the limited farmland resources of China, exploring an effective technology to repair contaminated soils is urgent and necessary. In this study, three technologies were employed, including variety screening, water management and foliage dressing, to assess their abilities to reduce the accumulation of Cd and As in the grains of different rice varieties, and meanwhile monitor the related yields. The results of variety screening under insufficient field drying condition showed that the As and Cd contents in the grains of only four varieties [Fengliangyouxiang 1 (P6), Zhongzheyou 8 (P7), Guangliangyou 1128 (P10), Y-liangyou 696 (P11)] did not exceed their individual national standard. P6 gained a relatively high grain yield but accumulated less As and Cd in the grains despite of the relatively high As and Cd concentrations in the rhizosphere soil. However, long-playing field drying in water management trial significantly increased Cd but decreased As content in the grains of all tested three varieties including P6, suggesting an important role of water supply in controlling the accumulation of grain As and Cd. Selenium (Se) showed a stronger ability than silicon (Si) to reduce As and Cd accumulation in the grains of Fengliangyou 4 (P2) and Teyou 524 (P13), and keep the yields. The results of this study suggest that combined application of water management and foliage dressing may be an efficient way to control As and Cd accumulation in the grains of paddy rice exposing to As- and Cd-contaminated soils. Highlights: Soil moisture is a key factor controlling the grain As and Cd contents. Rainfed cultivation significantly reduced grain As but increased grain Cd content. The variety of Fengliangyouxiang 1 is a desirable variety in variety screening trial. Se had a higher efficiency than Si to reduce the grain Cd and As contents. Use of water control and foliage dressing can control the grain As and Cd contents.